The Effect of Teamwork and Supervision On Employee Performance (Survey of Production Department Employee at CV. Sukahati Pratama Tasikmalaya) - Didah Nurhidayah; Barin Barlian; Mila Karmila (Penerbit Jurnal Indonesia, 2023)
This study aims to determine “The Effect of Teamwork and Supervision on Employee Performance in the Production Department of CV. Sukahati Pratama Tasikmalaya”. The population in this study amounted to 260 people and the sample used in this study were 43 people in the production division. This research method is quantitative using multiple linear regression. The result of this study are that teamwork and simultaneous supervision can have a significant effect on the performance of production employees at CV. Sukahati Pratama Tasikmalaya. Partially teamwork has no significant effect on employee performance in the production section of CV. Sukahati Pratama Tasikmalaya and Supervision partially have a significant effect on the perfoemance of employees in the production section of CV. Sukahati Pratama Tasikmalaya